Disrupting Dialogue? The Participatory Urban Governance of Far-Right Contestations in Cottbus - Gala Nettelbladt (Urban Planning, 2021)
This article investigates how municipal governments negotiate far-right contestations through the format of citizens' dialogues and contemplates to what extent they disrupt established assumptions about participatory urban governance. In doing so, I want to contribute to emerging scholarship on reactionary responses to migration-led societal transformations in cities via scrutinising their effects on institutional change in participatory practices. Building on participatory urban governance literature and studies on the far right in the social sciences, I argue that inviting far-right articulations into the democratic arena of participation serves to normalise authoritarian and racist positions, as the far right's demand for more direct involvement of 'the people' is expressed in reactionary terms. I will show how this applies to two prominent notions of participation in the literature, namely, agonistic and communicative approaches. This argument is developed through an explorative case study of two neighbourhood-based citizens' dialogues in Cottbus, East Germany, which the municipal government initiated in response to local far-right rallies. While a careful reading of these forums reveals productive potentials when the issue of international migration is untangled from context-specific, socio-spatial problems in the neighbourhoods, my analysis also shows how the municipality's negotiation of far-right contestations within the citizens' dialogues serves to legitimise far-right ideology. I find that to negotiate today's societal polarisation, municipal authorities need to rethink local participatory institutions by disentangling these complex dynamics and reject far-right contestations, while designing dialogues for democratic and emancipatory learning.
Keywords: 320; agonism; cities; communicative planning theory; far right; local democracy; municipal government; participation; populism; racism; urban governance